42.5k views
2 votes
Given f(x) = 4x - 3 and g(x) = 7x +5, find f(x) + g(x).

Given f(x) = 4x - 3 and g(x) = 7x +5, find f(x) + g(x).-example-1
User Tkhuynh
by
5.0k points

2 Answers

3 votes

Answer:

11x +2

Explanation:


f(x) = 4x - 3 \\g(x) = 7x +5\\\\f(x)+g(x) = \\\\4x-3 +(7x +5)\\\\=4x-3+7x+5\\\\=4x+7x-3+5\\\\=11x-3+5\\\\=11x+2

User Elliotching
by
5.3k points
4 votes

Answer:

Given f(x) = 2x + 3 and g(x) = –x2 + 5, find (g o f )(x).

(g o f )(x) = g( f(x))

= g(2x + 3)

= –( )2 + 5 ... setting up to insert the input

= –(2x + 3)2 + 5

= –(4x2 + 12x + 9) + 5

= –4x2 – 12x – 9 + 5

= –4x2 – 12x – 4

Explanation:

User Silverclaw
by
4.9k points